CASE REPORT: SEMI FOWLER POSITION AND SUCTION IN POST CRANIOTOMY PATIENTS - Nadia Faizah; Ida Nurjayanti; Lina Karunia (Jurnal Kesehatan Saintika Meditory, 2025)
Stroke is a pathological condition that occurs when cerebral blood flow is blocked or when nerve function is disrupted due to occlusion or rupture of vascular structures, culminating in necrosis of certain brain cells resulting in inadequate supply of nutrients and oxygen needed for optimal brain activity. Intracerebral hemorrhage (ICH) stroke, better known as hemorrhagic stroke, occurs when a blood vessel in the brain ruptures. This study aims to determine the effectiveness of the semi-Fowler position and suction in post-craniotomy patients with nursing problems related to the airway. The process of this case study includes assessment, nursing diagnosis, planning, and evaluation. The respondents in this study were 1 patient who was given a semi-Fowler position and suction for approximately 10 seconds after surgery. Case study after being given the semi-Fowler position and suction intervention, sputum production and rhonchi sounds decreased